Parasitismo do idiamin (Lagria villosa, F) por Hyalomodes brasiliensis Tns (Diptera: Tachinidae) e outros dípteros - Rocha de Oliveira , Jésus; Bastos Nogueira , Sebastião (Revista Ceres, 2025)
The coleopteran, Lagria villosa, introduced recently to Brazil, has become esta- blished at extremely high population densities, threatening cultivated plants in Brazil. Int the second third of 1977, an unusual decline in the Lagria population was observed. In a laboratory study of the insect, begun in August of 1976 by the entomology sector of the Federal University of Viçosa, the ocurrence of a dipteran parasite, Hyalomodes brasiliensis Tns. (Diptera:Tachinidae) was verified. Identification of this parasite was made bv C.W. Sabrosky of the Agriculture Research Center in Beltsville, Maryland. It represents the first parasite of Lagri villosa found in Brazil and may lead to control by a natural enemy. One other dipteran species has been collected and sent to Beltsville for identification.